1982
DOI: 10.1177/002221948201500501
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Megadoses of Selected B Complex Vitamins on Children with Hyperkinesis

Abstract: One hundred children with hyperkinesis and cerebral dysfunction were given individual three-day trials of pharmacologic doses of thiamin, calcium pantothenate, pyridoxine, and placebo. When beneficial response was noted, a second week-long trial of vitamins was given, alternating with placebo, followed by long-term therapy. Two-thirds of the remaining children not responding to this schedule were then given pharmacologic doses of niacinamide, combinations of B-complex vitamins, or elimination diets. Eight chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Though half or more of enriched samples selected for suspicion of food sensitivity seem to respond well under controlled conditions, it is not clear what proportion this represents of the whole ADHD population. Preliminary evidence suggests that the profile of a probable responder is a middle-or upper-class preschooler with atopy and prominent irritability and sleep disturbance, with physical as well as behavioral symptoms, and possibly high copper levels (Brenner, 1979), but the definition needs more work.…”
Section: Elimination Diets (Oligoantigenic or Few-food Diet)mentioning
confidence: 99%
See 1 more Smart Citation
“…Though half or more of enriched samples selected for suspicion of food sensitivity seem to respond well under controlled conditions, it is not clear what proportion this represents of the whole ADHD population. Preliminary evidence suggests that the profile of a probable responder is a middle-or upper-class preschooler with atopy and prominent irritability and sleep disturbance, with physical as well as behavioral symptoms, and possibly high copper levels (Brenner, 1979), but the definition needs more work.…”
Section: Elimination Diets (Oligoantigenic or Few-food Diet)mentioning
confidence: 99%
“…The third strategy, judicious use of single vitamins in megadosage to alter neural metabolism in specific ways, is actually more like psychopharmacology and has not been adequately explored despite some encouraging early reports (e.g., Coleman et al, 1979;Brenner, 1982).…”
Section: Vitamin Supplementationmentioning
confidence: 99%
“…It has been suggested that megavitamin therapy may be a useful adjunct in the treatment of ADHD (Cott 1972;Coleman et al 1979;Brenner 1982). In 1972, using doses of niacin, ascorbic acid, and pyridoxine from 100 to 300 times the recommended dietary allowance, Cott reported that megavitamin therapy decreased hyperactivity and improved both concentration and attention span, and subsequently learning capacity, in children with ADHD.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…Other children improved following pharmacological doses of thiamin, niacin, or a combination of B-complex vitamins with minerals. From his observations, Brenner (1982) concluded that while there are mUltiple causes for ADHD, in a significant number of cases the disorder is the result of vitamin deficiencies.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…to high-dose thiamin (Brenner, 1982). Improved behavior has also 492 been reported in autistic children treated with TTFD, but the nature of 493 the improvements was not described (Lonsdale et al, 2002).…”
mentioning
confidence: 99%